QUBIC: The Q&U Bolometric Interferometer for Cosmology - A novel way to look at the polarized Cosmic Microwave Background - Mennella, Aniello; Ade, P. A. R.; Aumont, J.; Banfie, S.; Battaglia, P.; Battistelli, E. S.; Baùe, F.; Buzi, D.; Columbro, F.; Bélie, B.; Bennett, D.; Bergé, L.; et al. (Sissa, 2018)
Fil: Mennella, Aniello. University of Milan; Italia